Liquefaction analysis of alluvial soil deposits in Bedsa south west of Cairo - Kamal Mohamed Hafez Ismail Ibrahim (Ain Shams Engineering Journal, 2014)
Bedsa is one of the districts in Dahshour that lays south west of Cairo and suffered from liquefaction during October 1992 earthquake, Egypt. The soil profile consists of alluvial river Nile deposits mainly sandy mud with low plasticity; the ground water is shallow. The earthquake hypocenter was 18 km far away with local magnitude 5.8; the fault length was 13.8 km, as recorded by the Egyptian national seismological network (ENSN) at Helwan. The analysis used the empirical method introduced by the national center for earthquake engineering research (NCEER) based on field standard penetration of soil. It is found that the studied area can liquefy since there are saturated loose sandy silt layers at depth ranges from 7 to 14 m. The settlement is about 26 cm. The probability of liquefaction ranges between 40% and 100%. The presence of impermeable surface from medium cohesive silty clay acts as a plug resisting and trapping the upward flow of water during liquefaction, so fountain and spouts at weak points occurs. It is wise to use point bearing piles with foundation level deeper than 14 m beyond the liquefiable depth away from ground slopes, otherwise liquefaction improving techniques have to be applied in the area.